From statism to neo-liberalism : the development process in India - Upadhyay, V; Upadhyay, V.; National Committee for Celebration of Birth Centenary of Prof. D.R. Gadgil; Indian Political Economy Association (Delhi : Daanish Books, 2009)
Papers presented at a seminar organized jointly by National Committee for Celebration of Birth Centenary of Prof. D.R. Gadgil and Indian Political Economy Association.
Includes index.
Includes statistical tables.
Includes bibliographical references.
Keywords: India -- Economic policy -- 1991- -- Congresses; India -- Economic policy -- 1991- -- Statistics -- Congresses